Diagnóstico del sistema turístico del cantón Milagro y determinación de estrategias para su desarrollo turístico - Coronado, F. (2010)
This investigation was realized in Milagro town, which is located in province of Guayas. This paper presents a diagnostic of the tourism system of Milagro and strategies which objective is to help to tourism development of Milagro. Here you will find concepts of tourism system how: offer, infrastructure, tourists attractive, demand, community and superstructure, and the methodology of investigation used to elaborate this paper. Also there is information about Milagro town its history, geography, economic and demography to know more about Milagro and its habitants. If you continue reading you can find an analysis of tourist situation of Milagro although its offer, infrastructure, tourists attractive, demand, community and superstructure with the objective of elaborate a FODA analysis. Also you will find how is working the tourism system of Milagro and its failures. At last there are strategies which were created to help to tourism development of Milagro town.